2020
DOI: 10.1101/2020.04.29.050567
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network Analysis Prioritizes DEWAX and ICE1 as the Candidate Genes for Major eQTL Hotspots in Seed Germination

Abstract: 18Seed germination is characterized by a constant change of gene expression across different time points. These 19 changes are related to specific processes, which eventually determine the onset of seed germination. To get a better 20 understanding on the regulation of gene expression during seed germination, we performed a quantitative trait 21 locus mapping of gene expression (eQTL) at four important seed germination stages (primary dormant, after-22 ripened, six-hour after imbibition, and radicle protrusion… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 75 publications
(17 reference statements)
2
7
0
Order By: Relevance
“…mRNA abundances) in the seeds of a tomato RIL population that had matured in different maternal nutrient environments, we show that the maternal environment affects both regulation and the genetic architecture of gene expression in progeny seeds. Especially, trans eQTLs proved environment specific, which is comparable to other species [57,[63][64][65][66][67][72][73][74]. We found 3,833 genes (~26% of all detected expressed genes in the RILs), with an eQTL in HP and 6,815 genes (~46% of all expressed genes in the RILs) with an eQTL in LN.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…mRNA abundances) in the seeds of a tomato RIL population that had matured in different maternal nutrient environments, we show that the maternal environment affects both regulation and the genetic architecture of gene expression in progeny seeds. Especially, trans eQTLs proved environment specific, which is comparable to other species [57,[63][64][65][66][67][72][73][74]. We found 3,833 genes (~26% of all detected expressed genes in the RILs), with an eQTL in HP and 6,815 genes (~46% of all expressed genes in the RILs) with an eQTL in LN.…”
Section: Discussionsupporting
confidence: 72%
“…Combining the wealth of information obtained by mapping eQTLs enables (re)construction of regulatory networks underlying plant traits [56,60,62]. In addition, comparison of eQTL profiles from multiple environments may aid our understanding of how genetic variation shapes the effects the environment has on the appearance of phenotypes [57,63,64]. In plant (Arabidopsis) and worm (Caenorhabditis elegans) model systems it has been shown that especially trans-eQTLs are dynamic and can be highly specific for a certain environment [57,[63][64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%
“…Heritable variation in these molecular phenotypes often plays a role in heritable phenotypic variation ( Jimenez-Gomez et al 2010 ; Schmid et al 2015 ; Sterken et al 2017 ). Mapping expression QTLs (eQTLs) can provide insight into the transcriptional architecture of complex traits and have been conducted in model species such as Arabidopsis thaliana and C. elegans as well as several other taxa ( Li et al 2006 ; Keurentjes et al 2007 ; West et al 2007 ; Li et al 2010 ; Rockman et al 2010 ; Vinuela et al 2010 ; Snoek et al 2012 , 2017 ; Cubillos et al 2014 ; Ranjan et al 2016 ; Sterken et al 2017 , 2019 ; Hartanto et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Heritable variation in these molecular phenotypes often plays a role in heritable phenotypic variation [10,30,33]. Mapping expression QTLs (eQTLs) can provide insight into the transcriptional architecture of complex traits and have been conducted in model species such as Arabidopsis thaliana and C. elegans as well as several other taxa [26,[28][29][30][31][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Most eQTL studies have been done on populations of recombinant inbred lines (RILs) originating from a cross between two different parental genotypes [26,[28][29][30][31][34][35][36][37][38][39][40]. Inclusion of more than two parents can capture more genetic variation, increasing the number of detected QTLs, potentially allowing more precise mapping and therefore reducing the number of potential candidate causal genes to be verified [42].…”
Section: Introductionmentioning
confidence: 99%